TRANSFORMATION OF MAQÂSHID Al-SYARÎ’AH (An Overview of the Development of Islamic Law in Indonesia) - Absori .; Aidul Fitriciada Azhari; M. Mu’inudinillah Basri; Fatkhul Muin (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2016)
Abstract:This study is part of an effort to systematize the basic conception of the values of the sharia as the foundation in the life of nation and state life, where the orientation is to embody the essence of the religious life through the maqâshid al-syarî`ah. Islam as al-dîn has been providing the basics of life of Muslims through the al-Qur’an and as-Sunnah. Both of these contain guidance values of human life, including in running the sharia for Muslims. Sharia (syarî`ah) in perspective of terminology is "street". In an isthilâhî perspective, it is a way to get to God. The basic meaning of sharia itself should be realized in the basic understanding maqâshid al-syarî`ah, which can be interpreted within the scope of statehood, because the meaning contained are the values of universality of maqâshid al-syarî`ah. In the context of Indonesian, then maqâshid al-syarî`ah is part of the basic conception air Almighty God with the aim of creating prosperity for the people of Indonesia. In this study, the approach used is the doctrinal bases to study literature. This study is the strengthening of the maqâshid al-syarî`ah as the basis for the development of Islamic law.Abstrak:Kajian ini merupakan bagian dari upaya untuk sistematisasi konsep dasar dari nilai-nilai syari’ah sebagai pondasi dalam kehidupan berbangsa dan kehidupan bernegara, dimana orientasi tersebut adalah untuk mewujudkan hakikat kehidupan dalam beragama melalui maqâshid al-syarî`ah. Islam sebagai al-dîn telah memberikan dasar-dasar kehidupan umat Muslim melalui al-Qur’an dan al-Sunnah. Kedua hal tersebut mengandung nilai-nilai tuntunan kehidupan umat manusia termasuk dalam menjalankan syariah bagi umat Muslim. Syari’ah dalam perspektif terminologi merupakan “jalan”. Sedangkan secara isthilâhî, ia dimaknai sebagai jalan untuk sampai kepada Allah SWT. Makna dasar dari syari’ah itu sendiri harus diwujudkan dalam pemahaman dasar maqâshid al-syarî’ah, di mana dapat dimaknai dalam cakupan kehidupan bernegara, karena makna yang terkandung adalah nilai-nilai universalitas dari maqâshid al-syarî`ah. Dalam konteks keindonesiaan, maka maqâshid al-syarî`ah merupakan bagian dari konsepsi dasar berketuhanan Yang Maha Esa dengan tujuan menciptakan kesejahteraan bagi rakyat Indonesia. Dalam kajian ini, pendekatan yang digunakan adalah pendekatan doktrinal dengan mendasarkan kepada kajian kepustakaan. Kajian ini merupakan penguatan maqâshid al-syarî`ah sebagai dasar pem-bangunan hukum Islam.